PERANAN KEPEMIMPINAN KEPALA DESA UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA (Studi Kasus Desa Sukandebi Kecamatan Naman Teran Kabupaten Karo) - Sitepu, Masta Manita Br; Degodona, L. Primawati; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study examines how the Role of Village Head Leadership to Increase Community Participation in Sukandebi Village Development, Naman Teran District, Karo Regency. This research method uses descriptive qualitative research, data collection is obtained through interviews and documentation then processed into narrative form. Key informants in this study are the Head of Sukandebi Village and the Secretary of Sukandebi Village, the main informant is the Village Consultative Body (BPD) of Sukandebi Village and additional informants are the people of Sukandebi Village. The results of this study concluded that the role of the village head to increase community participation in the development of Sukandebi Village, Naman Teran District, Karo Regency, has very good leadership in carrying out his function as the head of Sukandebi village. The village head not only carries out development deliberations, the village head also invites and motivates the community to always work together to carry out mutual cooperation in the development of Sukandebi Village. The low level of human resources, education, and awareness as well as the economic conditions of the community in Sukandebi Village affect their level of participation in village development. Highly educated people can help facilitate the efforts of the village head in conveying information about development programs. It is hoped that the role of the village head in driving community participation efforts in village development activities needs to be maintained and improved.